HERPESTES AUROPUNCTATUS AS A NEW RESERVOIR HOST OF TRICHINELLA SPIRALIS IN IRAN - GH. Mowlavi; J. Massoud; MB. Rokni (Tehran University of Medical Sciences, 2000)
A new reservoir host of Trichinella was identified as: Herpestes auropunctatus, (Mangoose) in province of Khuzestan, south west of Iran. Wild swine, brown bear jackal and wild cat have been reported as natural host for Trichinella so far. The larvae obtained from the mongoose was infective for rat and white mouse, but the latter was more sensitive comparatively (This study was carried out in the Ahwaz Health Research Station).